2020
DOI: 10.1186/s12870-020-02624-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses of leaf gas exchange attributes, photosynthetic pigments and antioxidant enzymes in NaCl-stressed cotton (Gossypium hirsutum L.) seedlings to exogenous glycine betaine and salicylic acid

Abstract: Background Application of exogenous glycine betaine (GB) and exogenous salicylic acid (SA) mitigates the adverse effects of salinity. Foliar spraying with exogenous GB or SA alleviates salt stress in plants by increasing leaf gas exchange and stimulating antioxidant enzyme activity. The effects of foliar application of exogenous GB and SA on the physiology and biochemistry of cotton seedlings subjected to salt stress remain unclear. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 75 publications
5
51
0
Order By: Relevance
“…In a previous study, we found exogenous foliar-applied GB significantly enhanced the endogenous accumulation of GB but had a non-significant effect on the accumulation of endogenous SA compared with changes under NaCl stress without supplementation. In contrast, the SA-containing foliar spray significantly stimulated both endogenous GB and SA accumulation [37]. In agreement with our observations, exogenously sprayed SA ameliorated the accumulation of endogenous GB in Vigna radiata subjected to salinity stress [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a previous study, we found exogenous foliar-applied GB significantly enhanced the endogenous accumulation of GB but had a non-significant effect on the accumulation of endogenous SA compared with changes under NaCl stress without supplementation. In contrast, the SA-containing foliar spray significantly stimulated both endogenous GB and SA accumulation [37]. In agreement with our observations, exogenously sprayed SA ameliorated the accumulation of endogenous GB in Vigna radiata subjected to salinity stress [19].…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, we observed that as a response to 150 mM NaCl stress, the endogenous biosynthesis of GB and SA was significantly increased compared with the wellwatered treatment control [37]. Our findings are in good agreement with those of Chen and Murata [38,39], who reported that plants synthesize GB under environmental stress, including salinity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…M. hupehensis is one of the most popular rootstocks for apple production and cultivation ( Su et al, 2020 ) but unfortunately suffers from serious KCl stress due to the huge amount of potassium fertilizer applied to orchards ( Zheng et al, 2021 ). Introducing exogenous substances such as plant growth regulator, osmotic adjustment substances, and antioxidants effectively alleviates salt stress ( Li et al, 2012 ; Chen et al, 2019 ; Hamani et al, 2020 ). As an antimicrobial phytoalexin, Res has an effect on high boron in pepper plants and alleviates NaCl stress in citrus seedlings ( Kostopoulou et al, 2014 ; Sarafi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…M. hupehensis is one of the most popular rootstocks for apple production and cultivation [51], but unfortunately suffers from serious KCl stress due to the huge amount of potassium fertilizer applied to orchards. Introducing exogenous substances such as plant growth regulator, osmotic adjustment substances, and antioxidants effectively alleviates salt stress [52,53,54]. As an antimicrobial phytoalexin, Res alleviates NaCl stress in citrus seedlings [42].…”
Section: Discussionmentioning
confidence: 99%